Analysis of the effectiveness of bronchoscopic methods in the diagnosis of lung cancer - Andrychiewicz, Andrychiewicz; Sega, Aurelia; Sładek, Krzysztof (Nursing in the 21st Century, 2013)
ANALYSIS OF THE EFFECTIVENESS OF BRONCHOSCOPIC METHODS IN THE DIAGNOSIS OF LUNG CANCER Introduction. Lung cancer is the most common malignant cancer in men, with high mortality rate – mainly due to the late diagnosis established in advanced stage of the disease. Aim. The study aimed to assess the usefulness of endoscopic diagnostic methods performed in patients with suspected lung cancer. Materials and methods. A retrospective analysis of available medical documentation of bronchofiberoscopic procedures of 124 patients suspected for lung cancer and diagnosed in the Invasive Diagnostics Department of the Chest Diseases in 2011. In the analysis, the researchers thoroughly examined the description of the macroscopic changes in the bronchial tree, and analyzed the cytology and histology results. Results. The accuracy of bronchofiberoscopic methods in diagnosing lung carcinoma was 55.7% and was dependent on the size and localization of the lung tumor. In case of isolated changes, the accuracy was 49%, and if changes were localized in two bronchi – 87.5%. When the main carina was distended, the accuracy was 74.6% with the use of standard transbronchial nodular aspiration biopsy (TBNA). Based on the cytology of the bronchoalveolar lavage, carcinoma was diagnosed in 42% patients. Conclusions. The localization and size of the process has an im pact on the diagnostic per form ance of endo scopic methods in patients suspected for lung carcinoma. The chances of establishing the diagnosis are in creased when TBNA of mediastinal lymph nodes is performed. The bronchoalveolar lavage cytology is an effective diagnostic method only in advanced process with macroscopic changes visible in the bronchial tree during bronchoscopic examination.